Синтез алгоритмов критического управления с учетом влияния окружающей среды - Тимофеев, В. А. (ХНУРЭ, 2004)
In this paper input signals spaces that are used in critical control systems synthesis are considered and analyzed. The control law structure for ARMAX-plant in spaces and are proposed.
Keywords: критическое управление; система критического управления; синтез алгоритмов; распределение сигналов и помех